Documentary control of the canton of San Joaquín de Flores, Heredia, from 1880 to 2006. - Chaverri Fernández, María Cecilia (2012)
This document summarizes the final graduation work on a documentary control carried out in the canton of San Joaquín de Flores in the province of Heredia, covering the period from 1880 to 2006. This paper presents the objectives that structured the research, a brief contextualization on the documentary control, the methodology used and finally conclusions.